2021
DOI: 10.1111/1365-2656.13421
|View full text |Cite
|
Sign up to set email alerts
|

Merging dynamical and structural indicators to measure resilience in multispecies systems

Abstract: 1. Resilience is broadly understood as the ability of an ecological system to resist and recover from perturbations acting on species abundances and on the system's structure. However, one of the main problems in assessing resilience is to understand the extent to which measures of recovery and resistance provide complementary information about a system. While recovery from abundance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Additionally, the scale at which this analysis occurs, whether the population or community level, is important. Our results show that a community's distributions of abundance and information flow are potentially more informative about the habitat than its diversity, similar to [57], who demonstrated how structural and dynamical indicators were sufficient for measuring system health. Although some studies have equated diversity with ecosystem health, some have found that diseased habitats can display higher microbial diversity than healthy habitats, particularly because of an increase in viruses [58][59][60].…”
Section: Phylogenetic and Probabilistic Ecohealth Characterizationsupporting
confidence: 77%
“…Additionally, the scale at which this analysis occurs, whether the population or community level, is important. Our results show that a community's distributions of abundance and information flow are potentially more informative about the habitat than its diversity, similar to [57], who demonstrated how structural and dynamical indicators were sufficient for measuring system health. Although some studies have equated diversity with ecosystem health, some have found that diseased habitats can display higher microbial diversity than healthy habitats, particularly because of an increase in viruses [58][59][60].…”
Section: Phylogenetic and Probabilistic Ecohealth Characterizationsupporting
confidence: 77%
“…local asymptotic stability (May, 1972). Hence, we can hypothesize a similar negative relationship between complexity and the amplitude of the feasibility domain (Arnoldi & Haegeman, 2016;Gibbs et al, 2018;Medeiros et al, 2021). In multi-trophic communities, this complexity is encoded in the number of species across different trophic guilds and their interactions with species of the same and other guilds.…”
Section: Introductionmentioning
confidence: 81%
“…In this Special Feature, Medeiros et al. (2021) reveal that recovery and resistance are negatively correlated with one another using both experimental microbial systems and theoretical models, suggesting that resistance could be inferred from recovery and vice versa. Likewise, Jones et al.…”
Section: Opportunities and Challenges In The Special Featurementioning
confidence: 99%
“…Combining theoretical studies with experiments and/or observational studies can also help to test the validity of resilience concepts (Li et al, 2021;Medeiros et al, 2021).…”
Section: Contributi On S To This S Pecial Fe Atu R Ementioning
confidence: 99%
See 1 more Smart Citation